2022
DOI: 10.3389/fphar.2022.981578
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis-induced AKI: From pathogenesis to therapeutic approaches

Abstract: Sepsis is a heterogenous and highly complex clinical syndrome, which is caused by infectious or noninfectious factors. Acute kidney injury (AKI) is one of the most common and severe complication of sepsis, and it is associated with high mortality and poor outcomes. Recent evidence has identified that autophagy participates in the pathophysiology of sepsis-associated AKI. Despite the use of antibiotics, the mortality rate is still at an extremely high level in patients with sepsis. Besides traditional treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 152 publications
0
11
0
Order By: Relevance
“…The commonly affected organs include the heart, lungs, liver, brain, intestine, and kidneys. During sepsis, activation of the sympathetic nervous system, the release of vasoactive substances, and endothelial injury, together contribute to the redistribution of blood flow and microcirculation disturbances (3). These factors remarkably damage the kidney tissue (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The commonly affected organs include the heart, lungs, liver, brain, intestine, and kidneys. During sepsis, activation of the sympathetic nervous system, the release of vasoactive substances, and endothelial injury, together contribute to the redistribution of blood flow and microcirculation disturbances (3). These factors remarkably damage the kidney tissue (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies suggested that the maintenance of renal function depended on renal perfusion with su cient renal blood ow, and renal underperfusion was considered the key to the occurrence of SA-AKI. However, in recent years, the mechanism of microcirculation damage has constantly challenged this paradigm standard [13]. AKI can occur even if early, aggressive rehydration maintains adequate renal blood perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis can cause organ dysfunction and is a principal cause of death in critically ill patients. Acute kidney injury (AKI) is a common complication in septic patients, and about 60% of septic patients develop AKI [ 3 ]. Indeed, sepsis is a leading cause of AKI in critically ill patients and accounts for 45–70% of all AKI cases [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acute kidney injury (AKI) is a common complication in septic patients, and about 60% of septic patients develop AKI [ 3 ]. Indeed, sepsis is a leading cause of AKI in critically ill patients and accounts for 45–70% of all AKI cases [ 3 ]. It has also well known that AKI is associated with an increased risk of developing chronic kidney disease [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation